Clinical consequences of road traffic injuries among the elderly in Japan - Uno Hajime; Nagata Takashi; Perry Melissa J (BMC, 2010)
Abstract Background Road traffic injuries among the elderly have recently become a public health issue; therefore, we investigated the clinical characteristics of such injuries among the elderly in Japan. Methods A retrospective study was performed using data from a medium-sized hospital emergency department. Data were extracted from medical records for one year, and patients were categorized into groups ages 18-64, 65-74 and 75+. Variables included demographic characteristics, injury circumstances, and nature of injury. Univariate and bivariate descriptive statistical analyses were performed, and multivariate logistic regression was used to evaluate injury severity and hospital admission by age groups. Results A total of 1,656 patients were studied. Patients aged 65+ had more chest wall injury, intracranial injury, lower extremity fracture, and intrathoracic injury than patients aged 18-64. Conclusions Injury circumstances and nature of injuries associated with traffic incidents showed different patterns by age groups, particularly among the elderly.